Pengaruh Pembelajaran Micro Teaching Terhadap Kesiapan Diri Melaksanakan PPL Mahasiswa PAI - Azka Sabiila, Muhammad Zulfa; Mubarok, Ramdanil; Faruk Fauzi, Muhammad Ibnu (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
The aim of this research is to find out how much influence Micro Teaching learning has on the readiness to carry out PPL for PAI study program students. This research uses quantitative research and includes population research. The data source is data from the results of distributing questionnaires. The technique for collecting data is a questionnaire. Data validity was obtained through the results of validity tests of 40 respondents. The data analysis technique uses simple linear regression analysis. The results of the Simple Linear Regression Test in this study obtained a constant value (a) of 12,030, which means that the consistent value of the Micro Teaching Learning variable is 12,030, and self-readiness to carry out PPL (b/ regression coefficient) is 0.780, which states that the addition of 1% of Learning Micro Teaching, then the value of self-readiness to carry out PPL increases by 0.780, then the Simple Linear Regression equation Y= 12,030 + 0.780 means the influence is strong or high and the R Square value is 0.404, which means this research has a positive influence of 40.4%. Based on the results above, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, so it can be concluded that there is a positive influence on Micro Teaching Learning on the Readiness of Carrying out PPL for PAI Study Program Students at Sangatta Islamic College (STAI) of 40, 4% and 59.6% are influenced by other factors.